A High-Field Anodic NiO Nanosponge with Tunable Thickness for Application in p-Type Dye-Sensitized Solar Cells - Sultan, Umair; Ahmadloo, Farzaneh; Cha, Gi; Gökcan, Baris; Hejazi, Seyedsina; Yoo, Jeong Eun; Nguyen, Nhat Truong; Altomare, Marco; Schmuki, Patrik; Killian, Manuela (ACS Applied Energy Materials, 2020)
Dye-sensitized photocathodes have the potential to significantly contribute to the efficiency of the solar light-to-current conversion in tandem dye-sensitized solar cells (DSSCs). A novel, highly porous nanoarchitecture of NiO is developed in this project. The spongelike material is grown by anodization, shows a virtually crack-free morphology, strongly adheres to the substrate, and can be grown with a controllable thickness of at least up to 6.5 mu m. The oxide composition is NiO and the nanosponge exhibits p-type semiconductive behavior. A doubling of the maximum reported p-type DSSC efficiency compared to coumarin C343-sensitized NiO nanoparticle photocathodes can be achieved with the NiO nanosponge. The developed dye-sensitized p-type NiO-based cathodes are promising for application as photocathodes in tandem DSSC devices.
CRIS-Team WoS Importer:2020-09-18

Alkali Metal Cation Incorporation in Conductive TiO2 Nanoflakes with Improved Photoelectrochemical H2 Generation - Khorashadizade, Elham; Mohajernia, Shiva; Hejazi, Seyedsina; Mehdipour, Hamid; Naseri, Naimeh; Moradlou, Omran; Liu, Ning; Moshfegh, Alireza Z.; Schmuki, Patrik (ChemElectroChem, 2020)
In this research, we investigate the effect of alkali metal cations including Li, Na and Cs in hydrothermal solution on the morphology, stability, and photoactivity of nanostructured TiO2 nanoflakes as a photoanode. The TiO2 nanoflakes are formed through hydrothermal treatment of Ti foil in 1.0 M LiOH, NaOH or CsOH at 100 °C for 3 h. By subsequent thermal reduction of the structure in an optimized Ar/H2 environment, conductive TiO2 nanoflakes were formed. The reduction treatment remarkably improves the photocurrent density of the TiO2 nanoflakes and has the highest impact on the sample treated in the NaOH alkali solution. For the nanoflakes produced in NaOH alkali solution, the bandgap is shifted to a lower value and the structure shows the most stable morphology after thermal treatment compared to nanoflakes formed in other alkali solutions. Such reduced hydrothermally treated nanoflakes formed in NaOH can generate a photocurrent density of approximately 1 mA/cm−2 vs. Ag/AgCl in 1.0 M KOH solution, which is six times higher than for pristine TiO2.
CRIS-Team Scopus Importer:2020-04-28
Keywords: hydrogen generation; hydrothermal; nanoporous; reduction; titanium oxide

A long-term stable aqueous aluminum battery electrode based on one-dimensional molybdenum-tantalum oxide nanotube arrays - Jin, Bowen; Hejazi, Seyedsina; Chu, Hongqi; Cha, Gi; Altomare, Marco; Yang, Min; Schmuki, Patrik (Nanoscale, 2021)
Aluminum ion aqueous batteries (AIBs) are among the most promising candidates for high energy density devices due to the multivalent redox processes associated with Al3+ ion intercalation. However, only a few stable AIB electrode materials have been reported so far. MoO3 is a very promising electrode material due to its octahedral layered crystal structure which can accommodate multivalent cation by intercalation. However, the poor electrochemical stability of MoO3 and the sluggish intercalation kinetics of Al3+ ion in Mo oxides electrodes limit its practical application. In this work, we propose a strategy to overcome such shortcomings of MoO3 by fabricating electrodes composed of self-ordered one-dimensional (1D) MoTaOx nanotubes synthesized via electrochemical anodization of Mo-Ta alloy substrates. We show that this approach allows for direct incorporation of Ta in the Mo oxide nanotubes. The resulting MoTaOx nanotubes, composed of octahedral MoO3 and rhombohedral Mo2Ta2O11 phases, exhibit remarkable electrochemical stability and Al-ion storage properties in aqueous electrolytes that are superior to that of pristine Mo oxide or other most efficient electrode materials reported to date. Such MoTaOx nanotube-based electrodes can achieve a specific capacity of 1180 mA h cm-3 (337 mA h g-1, 141 µA h cm-2) at 1.25 A cm-3 ( 0.35 A g-1, 0.15 mA cm-2). More importantly, the capacity retention of such nanotube array electrodes remains above 83% of the initial capacity after 3000 cycles.
CRIS-Team Scopus Importer:2021-04-16

Amorphous Mo-Ta Oxide Nanotubes for Long-Term Stable Mo Oxide-Based Supercapacitors - Jin, Bowen; Hejazi, Seyedsina; Pyczak, Florian; Oehring, Michael; Mohajernia, Shiva; Kment, Stepan; Tomanec, Ondrej; Zboril, Radek; Nguyen, Nhat Truong; Yang, Min; Schmuki, Patrik (ACS Applied Materials and Interfaces, 2019)
With a large-scale usage of portable electric appliances, a high demand for increasingly high-density energy storage devices has emerged. MoO3 has, in principle, a large potential as a negative electrode material in supercapacitive devices due to high charge densities that can be obtained from its reversible redox reactions. Nevertheless, the extremely poor electrochemical stability of MoO3 in aqueous electrolytes prevents a practical use in high capacitance devices. In this work, we describe how to overcome this severe stability issue by forming amorphous molybdenum oxide/tantalum oxide nanotubes by anodic oxidation of a Mo-Ta alloy. The presence of a critical amount of Ta oxide (>20 at. %) prevents the electrochemical decay of the MoO3 phase and thus yields an extremely high stability. Due to the protection provided by tantalum oxide, no capacitance losses are measureable after 10,000 charging/discharging cycles.
CRIS-Team Scopus Importer:2019-12-10
Keywords: cycle stability; Mo oxide; nanotubes; supercapacitor; Ta oxide

As a single atom Pd outperforms Pt as the most active co-catalyst for photocatalytic H2 evolution - Cha, Gi; Hwang, Imgon; Hejazi, Seyedsina; Dobrota, Ana S.; Pašti, Igor A.; Osuagwu, Benedict; Kim, Hyesung; Will, Johannes; Yokosawa, Tadahiro; Badura, Zdeněk; Kment, Štěpán; Mohajernia, Shiva; et al. (iScience, 2021)
Here, we evaluate three different noble metal co-catalysts (Pd, Pt, and Au) that are present as single atoms (SAs) on the classic benchmark photocatalyst, TiO2. To trap the single atoms on the surface, we introduced controlled surface vacancies (Ti3+-Ov) on anatase TiO2 nanosheets by a thermal reduction treatment. After anchoring identical loadings of single atoms of Pd, Pt, and Au, we measure the photocatalytic H2 generation rate and compare it to the classic nanoparticle co-catalysts on the nanosheets. While nanoparticles yield the well-established the hydrogen evolution reaction activity sequence (Pt > Pd > Au), for the single atom form, Pd radically outperforms Pt and Au. Based on density functional theory (DFT), we ascribe this unusual photocatalytic co-catalyst sequence to the nature of the charge localization on the noble metal SAs embedded in the TiO2 surface.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Catalysis; Materials characterization; Nanomaterials

Boron-doped diamond (BDD) as an efficient back contact to thermally grown TiO2 photoelectrodes - Özkan, Selda; Ghanem, Hanadi; Mohajernia, Shiva; Hejazi, Seyedsina; Fromm, Timo; Borchardt, Rudolf; Rosiwal, Stefan; Schmuki, Patrik (ChemElectroChem, 2019)
In the present work, we investigate the efficiency of TiO2 photoelectrode layers on boron-doped diamond foil (BDDF) in comparison with a classic conducting glass (fluorine-doped tin oxide, FTO) back contact. Crystalline thin TiO2 layers were prepared on the substrates by two different methods: (i) deposition of metallic Ti thin films followed by thermal oxidation to form TiO2 (TO-TiO2), (ii) reactive sputter deposition of TiO2 thin films and crystallization of these layers (SP-TiO2). Optimized layers show that TO-TiO2 films on BDDF deliver a significantly higher incident photon to current ifficiency (IPCE) compared to directly sputtered SP-TiO2 layers and these layers on BDDF also outperform FTO as a back contact. We ascribe this beneficial effect of the BDDF back contact to the formation of an intermediate conductive phase of Ti-carbides at the TO-TiO2/BDDF interface.

Comparison of the sputtered TiO2 anatase and rutile thin films as electron transporting layers in perovskite solar cells - Shahvaranfard, Fahimeh; Li, Ning; Hosseinpour, Saman; Hejazi, Seyedsina; Zhang, Kaicheng; Altomare, Marco; Schmuki, Patrik; Brabec, Christoph (Nano Select, 2021)
We examine comparatively the performance of sputtered TiO2 rutile and anatase thin films as an electron transport layer (ETL) inMAPbI3-based perovskite solar cells. Both anatase and rutile TiO2 ETLs are deposited (on fluorine-doped tin oxide [FTO] substrates) by magnetron sputtering in the form of nanocrystalline thin films. We systematically investigate the role of crystallographic phase composition of TiO2 ETLs on the photovoltaic performance of perovskite solar cells. The champion power conversion efficiencies (PCEs) of 18.4% and 17.7% under reverse scan mode are obtained for perovskite solar cells based on TiO2 anatase and TiO2 rutile ETL, respectively. The results show that the magnetron sputtering deposited ETLs differ from each other only in their phase composition while the overall performance of the devices is not greatly affected by the crystallographic phase of the TiO2 ETLs. Our results point to an important fact that for a proper and reliable comparison between the performance of TiO2 anatase and rutile ETLs, it is crucial to investigate films of similar morphology and structure that are synthesize under similar condition
Keywords: magnetron sputtering; perovskite solar cell; TiO2 anatase; TiO2 rutile

Composition Gradients in Sputtered Ti-Au Alloys: Site-Selective Au Decoration of Anodic TiO2 Nanotubes for Photocatalytic H2 Evolution - Hejazi, Seyedsina; Altomare, Marco; Mohajernia, Shiva; Schmuki, Patrik (ACS Applied Nano Materials, 2019)
Au nanoparticles at the surface of TiO2 can improve the photocatalytic H2 generation performances because of their electron transfer cocatalytic ability. The key to maximize the cocatalytic effect is a fine control over Au nanoparticle size and placement on the photocatalyst, in relation to parameters such as the TiO2 morphology, illumination wavelength and pathway, and light penetration depth in the photocatalyst. Here we present an approach for site-selective intrinsic decoration of anodic TiO2 nanotubes (TNs) with Au nanoparticles: we produce, by Ti and Au cosputtering, Ti-Au alloy layers that feature compositional gradients across their thickness; these layers, when anodized under self-ordering electrochemical conditions, can form Au-decorated TNs where the Au nanoparticle density and placement vary according to the Au concentration profile in the metal alloy substrates. Our results suggest that not only the amount but also the Au cocatalyst placement can strongly affect the photocatalytic H2 evolution performance of the TN layers. We demonstrate that when growing Au-decorated TNs, the use of Ti-Au substrates with a suitable Au compositional gradient enables a higher photocatalytic H2 generation performance compared to TNs classically grown with a homogeneous cocatalyst decoration. As a side effect, a proper placement of the cocatalyst nanoparticles allows for reducing the amount of noble metal without dumping the H2 evolution activity.
CRIS-Team Scopus Importer:2019-07-16
Keywords: anodization; Au nanoparticle; H; self-decoration; site-selective decoration; Ti-Au alloy; TiO

Conductive Cu-Doped TiO2 Nanotubes for Enhanced Photoelectrochemical Methanol Oxidation and Concomitant Hydrogen Generation - Mohajernia, Shiva; Hejazi, Seyedsina; Andryskova, Pavlina; Zoppellaro, Giorgio; Tomanec, Ondrej; Zboril, Radek; Schmuki, Patrik (ChemElectroChem, 2019)
Cu doping in titania is usually detrimental to the material's photoconductivity, which prevents the use of this combination in photoanodes. In this work, we produce TiO2 nanotube arrays intrinsically doped with copper and establish sufficient conductivity to use them as efficient photoanodes for methanol oxidation in a photoelectrochemical hydrogen generation setting. Firstly, Cu-doped TiO2 nanotubes were produced by anodizing a Ti-Cu binary alloy. By subsequent thermal reduction of the structure in an Ar/H-2 environment, conductive copper-doped TiO2 nanotubes (TiCuTN Ar/H-2) can be achieved with an approximately 10(3) times higher conductivity than the non-reduced material. When these reduced Cu-doped TiO2 nanotubes are used as photoanode, copper species embedded in the TiO2 wall catalyze the methanol oxidation reaction. As a result of the combined effect of conductivity and catalytic effect of Cu, such reduced Cu:TiO2 nanotubes can generate a photo-current of 0.76 mA cm(-2) at 1 V vs. RHE, under AM1.5 (100 mW/Cm-2) irradiation - in a 50:50 MeOH/water solution - this is 33 times higher than for pristine Cu:TiO2 nanotubes.
CRIS-Team WoS Importer:2019-04-04

Dewetted Au Nanoparticles on TiO2 Surfaces: Evidence of a Size-Independent Plasmonic Photoelectrochemical Response - Licklederer, Markus; Mohammadi, Reza; Nguyen, Nhat Truong; Park, Hyoungwon; Hejazi, Seyedsina; Halik, Marcus; Vogel, Nicolas; Altomare, Marco; Schmuki, Patrik (Journal of Physical Chemistry C, 2019)
We induce solid-state dewetting of thin Au films (nominal thickness of 0.5-10 nm) on flat TiO2 surfaces to produce Au nanoparticles with an average size tunable in the 3-200 nm range. Such Au-decorated TiO2 surfaces enable plasmonic photoelectrochemical water splitting under visible light illumination (450-750 nm), with a photon-to-current conversion efficiency that reaches a maximum for TiO2 surfaces decorated with similar to 30 nm sized Au particles. Optical measurements show, as expected, a red shift of the plasmon resonance with the increasing Au nanoparticle size. More interestingly, the photocurrent is found to peak for every photoanode at similar to 600 nm regardless of the Au nanoparticle size, i.e., the wavelength of maximum photocurrent is size-independent. Such a remarkable observation can be ascribed to a hot electron injection cutoff effect, i.e., can be explained in terms of the interband versus intraband transition scenario.
CRIS-Team WoS Importer:2019-07-30

Engineering of the Electron Transport Layer/Perovskite Interface in Solar Cells Designed on TiO2 Rutile Nanorods - Shahvaranfard, Fahimeh; Altomare, Marco; Hou, Yi; Hejazi, Seyedsina; Meng, Wei; Osuagwu, Emeka Benedict; Li, Ning; Brabec, Christoph; Schmuki, Patrik (Advanced Functional Materials, 2020)
The engineering of the electron transport layer (ETL)/light absorber interface is explored in perovskite solar cells. Single-crystalline TiO2 nanorod (NR) arrays are used as ETL and methylammonium lead iodide (MAPI) as light absorber. A dual ETL surface modification is investigated, namely by a TiCl4 treatment combined with a subsequent PC61BM monolayer deposition, and the effects on the device photovoltaic performance were evaluated with respect to single modifications. Under optimized conditions, for the combined treatment synergistic effects are observed that lead to remarkable enhancements in cell efficiency, from 14.2% to 19.5%, and to suppression of hysteresis. The devices show J(SC), V-OC, and fill factor as high as 23.2 mA cm(-2), 1.1 V, and 77%, respectively. These results are ascribed to a more efficient charge transfer across the ETL/perovskite interface, which originates from the passivation of defects and trap states at the ETL surface. To the best of our knowledge, this is the highest cell performance ever reported for TiO2 NR-based solar cells fabricated with conventional MAPI light absorber. Perspective wise, this ETL surface functionalization approach combined with more recently developed and better performing light absorbers, such as mixed cation/anion hybrid perovskite materials, is expected to provide further performance enhancements.
Keywords: defect passivation; PC61BM; perovskite solar cells; TiCl4; TiO2 nanorods

Forming a Highly Active, Homogeneously Alloyed AuPt Co-catalyst Decoration on TiO2 Nanotubes Directly during Anodic Growth - Bian, Haidong; Nguyen, Nhat Truong; Yoo, Jeong Eun; Hejazi, Seyedsina; Mohajernia, Shiva; Müller, Julian; Spiecker, Erdmann; Tsuchiya, Hiroaki; Tomanec, Ondrej; Sanabria Arenas, Beatriz Eugenia; Zboril, Radek; Li, Yang Yang; et al. (ACS Applied Materials and Interfaces, 2018)
Au and Pt do not form homogeneous bulk alloys as they are thermodynamically not miscible. However, we show that anodic TiO2 nanotubes (NTs) can in-situ be uniformly decorated with homogeneous AuPt alloy nanoparticles (NPs) during their anodic growth. For this, a metallic Ti substrate containing low amounts of dissolved Au (0.1 at%) and Pt (0.1 at%) is used for anodizing. The matrix metal (Ti) is converted to oxide while at the oxide/metal interface direct noble metal particle formation and alloying of Au and Pt takes place; continuously these particles are then picked up by the growing nanotube wall. In our experiments the AuPt alloy NPs have an average size of 4.2 nm and, at the end of the anodic process, are regularly dispersed over the TiO2 nanotubes. These alloyed AuPt particles act as excellent co-catalyst in photocatalytic H2 generation - with a H2 production of 12.04 μL h-1 under solar light. This represents a strongly enhanced activity as compared with TiO2 NTs decorated with monometallic particles of Au (7 μL h-1) or Pt (9.96 μL h-1)
Keywords: anodization; photocatalysis; TiO2 nanotubes; AuPt alloy nanoparticle; H2 evolution

Influence of Ti3+ defect-type on heterogeneous photocatalytic H2 evolution activity of TiO2 - Mohajernia, Shiva; Andryskova, Pavlina; Zoppellaro, Giorgio; Hejazi, Seyedsina; Kment, Stepan; Zboril, Radek; Schmidt, Jochen; Schmuki, Patrik (Journal of Materials Chemistry A, 2020)
Reduced titanium dioxide has recently attracted large attention, particularly for its unique co-catalyst-free heterogeneous photocatalytic application for H2 generation. The enhanced photocatalytic activity of the reduced TiO2 was previously ascribed to the introduction of point crystal defects (mainly Ti3+ centers), which result in the formation of intrinsic co-catalytic centers and enhanced visible light absorption. In this work, we systematically investigate the effect of different defects in the TiO2-x lattice on photocatalytic H2 evolution. To introduce different types of defects, thermal annealing in air (oxidative), Ar (inert), Ar/H2 (reducing), and H2 (reducing) atmospheres was performed on commercially available anatase nanopowder. Then, the powders were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HR-TEM) to clarify the effect of treatment on material properties. Furthermore, the defect types were characterized by electron paramagnetic resonance (EPR) spectroscopy. We show that thermal annealing in different atmospheres can form different amounts of different defect types in the TiO2 structure. The highest photocatalytic activation is achieved by annealing the anatase powder in a reducing atmosphere for an appropriate temperature/annealing time. By combining the results from H2 generation and EPR analysis we show that the simultaneous presence of two types of defects, i.e. surface exposed Ti3+ and lattice embedded Ti3+ centers in an optimum low concentration is the determining factor for an optimized photocatalytic H2 evolution rate. In fact, annealing anatase powder under the so-reported optimized conditions in reducing atmosphere leads to the generation of a considerable amount of H2, with rates as high as 338 μmol h-1 g-1
CRIS-Team Scopus Importer:2020-02-07

Intrinsically Ru-Doped Suboxide TiO2Nanotubes for Enhanced Photoelectrocatalytic H2Generation - Khorashadizade, Elham; Mohajernia, Shiva; Hejazi, Seyedsina; Mehdipour, Hamid; Naseri, Naimeh; Moradlou, Omran; Moshfegh, Alireza Z.; Schmuki, Patrik (Journal of Physical Chemistry C, 2021)
In the present research, we investigate the synergistic effects of Ru-doping and Ar/H2 reduction treatment on the photoelectrochemical water splitting performance and hydrogen evolution rate of TiO2 nanotube array photoelectrodes. The Ti-Ru alloy with 0.2 at. % Ru was used to grow anodic self-organized Ru-doped TiO2 nanotube layers. An ideal synergy between Ar/H2 reduction treatment and Ru-doping results in the extended absorption toward the visible light region and improved photoelectrocatalytic activity. The black Ru-doped TiO2-x photoanode's water splitting rate improves remarkably (∼ninefold) compared to the black TiO2-x sample (∼twofold). Moreover, the black Ru-doped TiO2-x photoanode shows a considerable increase in the H2 production rate (1.91 μmol h-1 cm-2) compared with the pristine TiO2 nanotube layer (0.044 μmol h-1 cm-2). We have also developed an ab initio model of pristine, Ru-doped, and Ru-doped hydrogenated TiO2 nanotubes to rationalize our experimental findings from the theoretical perspective.
CRIS-Team Scopus Importer:2021-04-09

Intrinsic Au-decoration on anodic TiO2 nanotubes grown from metastable Ti-Au sputtered alloys-High density co-catalyst decoration enhances the photocatalytic H-2 evolution - Hejazi, Seyedsina; Altomare, Marco; Nguyen, Nhat Truong; Mohajernia, Shiva; Licklederer, Markus; Schmuki, Patrik (Applied Materials Today, 2019)
Recent work demonstrated that intrinsic Au nanoparticle decoration of TiO2 nanotube arrays (NTs) can be achieved by electrochemical anodization of Ti-Au alloy substrates. However, for a Ti-Au cast alloy produced by melt-alloying, the Au concentration cannot exceed the solubility limit of Au in Ti of 0.2 at.% - this sets constraints on the intrinsic Au nanoparticle loading on anodic TiO2 NTs. Here we explore "metastable" Ti-Au metal substrates that are produced by Ti and Au cosputtering and we establish Au concentrations that far exceed the solubility limit in cast Ti-Au alloys. We show the use of these "metastable" Ti-Au sputtered layers for the anodic formation of TiO2 NTs with a much higher density of Au nanoparticle loading than using classic alloys. Under optimized conditions (Au nanoparticle density) photocatalytic H-2 production from such Au@TiO2 platforms provides a 15 times higher photocatalytic H-2 evolution rate than the best rates achieved with conventional alloys. (C) 2018 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-02-27

Intrinsic Cu nanoparticle decoration of TiO2 nanotubes: A platform for efficient noble metal free photocatalytic H2 production - Hejazi, Seyedsina; Mohajernia, Shiva; Wu, Yuhan; Andryskova, Pavlina; Zoppellaro, Giorgio; Hwang, Imgon; Tomanec, Ondrej; Zboril, Radek; Schmuki, Patrik (Electrochemistry Communications, 2019)
In this work, we grow intrinsically Cu-doped TiO2 nanotubes (TiNTs) by self-organizing anodization of Ti–Cu binary alloys. We demonstrate that up to a copper concentration of 1.5 at.% in the alloy, self-ordered Cu2+-doped nanotubes can be grown. Under UV illumination the Cu2+ ion-doped oxide structures can be converted to nanotubes that carry metallic nanoparticles (NPs) uniformly decorated on top of the TiNTs. We investigate the formation of these metallic nanoparticles under UV illumination by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and electron paramagnetic resonance (EPR). The resulting intrinsic copper-doped and decorated TiNTs have a strongly enhanced photocatalytic activity for H2 evolution in comparison to pristine TiNTs. Key is the light-induced conversion of the intrinsic Cu dopant to metallic copper nanoparticles that act as a stable co-catalyst for H2 generation.
CRIS-Team Scopus Importer:2019-09-10
Keywords: Cu doped TiO; Intrinsic copper decoration; Photocatalytic activity; TiO

Long-Living Holes in Grey Anatase TiO2 Enable Noble-Metal-Free and Sacrificial-Agent-Free Water Splitting - Liu, Ning; Mohajernia, Shiva; Nguyen, Nhat Truong; Hejazi, Seyedsina; Plass, Fabian; Kahnt, Axel; Yokosawa, Tadahiro; Osvet, Andres; Spiecker, Erdmann; Guldi, Dirk Michael; Schmuki, Patrik (Chemsuschem, 2020)
Titanium dioxide has been the benchmark semiconductor in photocatalysis for more than 40 years. Full water splitting, that is, decomposing water into H2 and O2 in stoichiometric amounts and with an acceptable activity, still remains a challenge, even when TiO2-based photocatalysts are used in combination with noble-metal co-catalysts. The bottleneck of anatase-type TiO2 remains the water oxidation, that is, the hole transfer reaction from pristine anatase to the aqueous environment. In this work, we report that “grey” (defect engineered) anatase can provide a drastically enhanced lifetime of photogenerated holes, which, in turn, enables an efficient oxidation reaction of water to peroxide via a two-electron pathway. As a result, a Ni@grey anatase TiO2 catalyst can be constructed with an impressive performance in terms of photocatalytic splitting of neutral water into H2 and a stoichiometric amount of H2O2 without the need of any noble metals or sacrificial agents. The finding of long hole lifetimes in grey anatase opens up a wide spectrum of further photocatalytic applications of this material.
CRIS-Team Scopus Importer:2020-08-21
Keywords: long-living holes; noble-metal-free; sacrificial-agent-free; titanium dioxide; water splitting

Metallic nanoparticle-on-mirror: Multiple-band light harvesting and efficient photocurrent generation under visible light irradiation - Tesler, Alexander; Sannomiya, Takumi; Hejazi, Seyedsina; Mohammadi Eslami, Reza; Vogel, Nicolas; Altomare, Marco; Schmuki, Patrik (Nano Energy, 2021)
We present a photoanode concept for photoelectrochemical (PEC) water splitting based on metal nanoparticles (Au, Ag, Cu) deposited on a Ti mirror (NPoM) to photosensitize an intermediate TiO2 layer to induce the harvesting of light with sub-bandgap photon energies. The generation of hot electron-hole pairs in metallic nanostructures can occur either by intraband excitation, i.e., plasmon electrons, or by the interband transition of the d-band electrons to the unoccupied conduction band states. Our results demonstrate that the underlying Ti mirror significantly amplifies the PEC activity of such NPoM systems in the visible spectral range. We show that the PEC enhancement in the visible spectral range is not limited to the intraband excitations but is affected mainly by the light trapping pathway within the TiO2 layer, i.e. due to a favorable interplay between thin-film interference cavity modes with both intraband and interband excitations. Among tested metals, Cu and Ag NPs demonstrate a 3-fold higher enhancement factor than that of Au NPs, while in both former cases the nature of the excited electrons is different. The experimentally determined internal quantum efficiency demonstrates alternating behavior with wavelength showing higher efficiencies at short wavelengths, which is attributed to the reduced Schottky barrier of the NPoMs at constructive interference maxima.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Fabry-Pérot interference; Interband excitations; Metallic nanoparticles; Photoelectrochemistry; Titanium dioxide; Water splitting

MoP-protected Mo oxide nanotube arrays for long-term stable supercapacitors - Bowen, Jin; Hejazi, Seyedsina; Hongqi, Chu; Mohajernia, Shiva; Nguyen, Nhat Truong; Min, Yang; Altomare, Marco; Schmuki, Patrik (Applied Materials Today, 2019)
In the current energy scenario, electrochemical capacitors hold the promise to fulfil requirements of high power densities, short charging-discharging times, and long lifetimes. For such supercapacitors, MoO3 is one of the most potent candidate as a negative electrode material, due to a very high theoretical charge density ascribed to easily-switchable multiple oxidation states. Nevertheless, the extremely poor electrochemical stability of MoO3 in aqueous electrolytes prevents any practical use. In the present work, we outline a strategy to overcome the poor stability of MoO3 electrodes: we produce by thermal phosphidation an amorphous MoP protective shell on Mo oxide nanotube arrays. This not only leads to an outstanding stability of the electrode but the phosphidized hybrid structures even maintains a capacitance as high as the initial capacitance (i.e. measured before deterioration) of unprotected pure oxide structures: the phosphidized hybrid structure, used as binder-free electrodes, can deliver a non-intercalation-based volumetric capacitance of over 2000 F cm−3 with an outstanding capacitance retention of ∼93% over 10,000 charging/discharging cycles.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Electrochemical stability; Mo oxide; MoP; Nanotubes; Supercapacitor; Volumetric capacitance

On the Controlled Loading of Single Platinum Atoms as a Co-Catalyst on TiO2 Anatase for Optimized Photocatalytic H2 Generation - Hejazi, Seyedsina; Mohajernia, Shiva; Osuagwu, Benedict; Zoppellaro, Giorgio; Andryskova, Pavlina; Tomanec, Ondrej; Kment, Stepan; Zbořil, Radek; Schmuki, Patrik (Advanced Materials, 2020)
Single-atom (SA) catalysis is a novel frontline in the catalysis field due to the often drastically enhanced specific activity and selectivity of many catalytic reactions. Here, an atomic-scale defect engineering approach to form and control traps for platinum SA sites as co-catalyst for photocatalytic H2 generation is described. Thin sputtered TiO2 layers are used as a model photocatalyst, and compared to the more frequently used (001) anatase sheets. To form stable SA platinum, the TiO2 layers are reduced in Ar/H2 under different conditions (leading to different but defined Ti3+-Ov surface defects), followed by immersion in a dilute hexachloroplatinic acid solution. HAADF-STEM results show that only on the thin-film substrate can the density of SA sites be successfully controlled by the degree of reduction by annealing. An optimized SA-Pt decoration can enhance the normalized photocatalytic activity of a TiO2 sputtered sample by 150 times in comparison to a conventional platinum-nanoparticle-decorated TiO2 surface. HAADF-STEM, XPS, and EPR investigation jointly confirm the atomic nature of the decorated Pt on TiO2. Importantly, the density of the relevant surface exposed defect centers—thus the density of Pt-SA sites, which play the key role in photocatalytic activity—can be precisely optimized.
CRIS-Team Scopus Importer:2020-03-17
Keywords: open-circuit H; photocatalysis; platinum; single-atom catalysis

On the material characteristics of a high carbon cast austenitic stainless steel after solution annealing followed by quenching in a CNT nanofluid - Pour-Ali, Sadegh; Kiani-Rashid, Ali-Reza; Babakhani, Abolfazl; Virtanen, Sannakaisa; Nguyen, Nhat Truong; Hejazi, Seyedsina; Davoodi, Ali; Nazarnejatizadeh, Afshin; Teimourinejad, Hashem (International Journal of Materials Research, 2019)
Solution annealing followed by quenching in carbon nanotubes (QCNT) nanofluid treatment was applied to generate very high interstitial carbon content, approximate to 0.30 wt.%, in an austenitic stainless steel (ASS). The high interstitial carbon content leads to remarkable improvement in mechanical properties with essentially no loss of ductility, with no chromium carbides and/or martensite formation. To evaluate the localized corrosion tendency and passivity behavior, 3.5 wt.% NaCl and borate buffer solutions were used, respectively. Based on the electrochemical corrosion results, both high carbon and low carbon (0.030 wt.%) QCNT-treated ASS alloys show comparable passivity and localized corrosion performance. In addition, Mott-Schottky plots revealed that the anodic films on QCNT-treated samples exhibit similar semiconducting characters.
CRIS-Team WoS Importer:2019-06-28

Photocatalytic H-2 Evolution: Dealloying as Efficient Tool for the Fabrication of Rh-decorated TiO2 Nanotubes - Sheikh Zadeh, Mohsen; Hejazi, Seyedsina; Mohajernia, Shiva; Tomanec, Ondrej; Mokhtar, Mohamed; Alshehri, Abdulmohsen; Sanjabi, Sohrab; Zboril, Radek; Schmuki, Patrik (ChemCatChem, 2019)
In this work, we report on a facile and novel method for decorating titanium dioxide (TiO2) nanotubes with Rh nanoparticle-nanonetworks that act as co-catalysts in photocatalytic H-2 generation. In a first step, a Ti-Rh (0.2 at%) alloy is etched in Kroll's solution leading to a dealloyed surface decorated with a Rh nanoparticle-network of adjustable geometry and loading. By subsequent anodization of the alloy samples, Rh:TiO2 nanotubes can be grown where the tube mouths are strongly decorated with the Rh nanoparticle network (RhNw). As evident from X-ray photoelectron spectroscopy (XPS) analysis, these Rh oxide Nws are converted to metallic Rh under UV irradiation. As a result, with time a steady increase of the H-2 evolution from the RhNw decorated TiO2 nanotubes is observed. Nanotubes carrying RhNw yield in photocatalytic experiments a 5-times higher H-2 evolution activity in comparison with nanotubes decorated by conventional Rh-sputtering (the same loading), and show a 228 times higher activity than pristine TiO2 nanotubes.
CRIS-Team WoS Importer:2019-10-22

Photo-Electrochemical Solar-to-Fuel Energy Conversion by Hematite-Based Photo-Anodes-The Role of 1D Nanostructuring - Hejazi, Seyedsina; Altomare, Marco; Schmuki, Patrik (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2019)
Photo-electrochemical (PEC) water splitting (WS) using metal oxide semiconductors is regarded as a promising approach for the renewable production of fuels and energy vectors such as hydrogen (H2). Among metal oxide semiconductors, iron oxide in the form of hematite (α-Fe2O3) is one of the most researched photo-anode materials, mainly due to its ability to absorb photons up to 600 nm combined to a set of desirable properties such as high photocorrosion resistance, environmental friendliness, large abundance and relatively low production costs. However, hematite main disadvantages are a low electrical conductivity and a high rate of charge recombination; both these shortcomings drastically limit functionality and efficiency of hematite-based photo-anodes in PEC devices. One-dimensional (1D) nanostructuring is a powerful tool to tackle such disadvantages as it provides the photoelectrode material with increased surface area along with directional charge transport properties and short charge diffusion distances to the electrolyte-these features can improve the lifetime of photo-generated charges and/or enhance the charge transfer efficiency, and can consequently lead to a superior photo-electrochemical performance. At the same time, chemical/physical modification can also compensate natural weaknesses of hematite in water photoelectolysis. The present mini-review outlines a series of most effective strategies for the fabrication of 1D hematite nanostructures as well as for their physicochemical modification, mainly by doping or co-catalyst decoration, to achieve superior PEC activity.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Hematite; Photoanode; photoelectrochemistry; semiconductors

Providing significantly enhanced photocatalytic H2 generation using porous PtPdAg alloy nanoparticles on spaced TiO2 nanotubes - Nguyen, Nhat Truong; Ozkan, S.; Hejazi, Seyedsina; Denisov, Nikita; Tomanec, Ondrej; Zboril, R.; Schmuki, Patrik (International Journal of Hydrogen Energy, 2019)
In the present work we introduce a simple approach to produce porous PtPdAg alloy nanoparticles on TiO2 nanotubes by a simple combined sputtering-dewetting-dealloying process. In a first step, three individual metals (Pt, Pd and Ag) were sequentially sputter-deposited on spaced TiO2 nanotubes, followed by a thermal dewetting treatment in Ar to convert these metal layers into ternary PtPdAg alloyed particles. Dealloying was carried out by a selective chemical dissolution of Ag in piranha solution that finally generated porous alloyed nanoparticles located on the TiO2 nanotube walls. The porous PtPdAg-decorated TiO2 nanotubes show enhanced photocatalytic H2 generation in comparison with porous Pt (67% increase) or any monometallic decoration (>120% increase). The photocatalytic enhancement is not only due to the increased number of active sites (larger surface area) of the porous particles but also due to the synergistic effects of the different alloying elements.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Dealloying; Dewetting; Photocatalytic H; PtPd alloy; TiO